Дослідження холоду при зберіганні ягід - Кюрчев, Сергій Володимирович; Верхоланцева, Валентина Олександрівна; Паляничка, Надія Олександрівна; Kiurchev, Serhii; Verkholantseva, Valentyna; Palianychka, Nadiia (Запоріжжя : 2023, 2023)
UA: Для того щоб зберегти ягоди в презентабельному, з погляду споживача, вигляді, необхідно створити оптимальні умови зберігання ягід, за яких припиняться або сильно сповільняться процеси гниття і псування. Тому, щоб створити правильні умови для зберігання ягідної продукції, необхідно застосовувати відповідну технологію. Інакше кажучи, десь можна обійтися просто приміщенням з хорошою професійною вентиляцією, а десь потрібна холодильна камера з регульованою атмосферою і системою мікробіологічного знезараження. Швидкість охолодження залежить не тільки від часу, температури і контакту з товаром, а також залежить від застосовуваного методу охолодження ягід. Існують різні технології охолодження і мають різні можливості для відведення тепла. Крім оптимальної температури та вологості повітря, треба враховувати фактор сумісності ягід під час зберігання. Не всі ягоди можна зберігати в одному об'ємі, тому що вони можуть впливати один на одного, виділяючи та поглинаючи речовини та запахи, які можуть вплинути на якість продукції. Ягідний ринок в нашій країні поки що тільки формується, тому розробка або впровадження дадуть більший вигідний спосіб зберігання. Стаття присвячена питанням дослідження існуючих технологій зберігання ягід. EN: The government program envisages perfection and development of complex In economic terms, berry freezing is a highly profitable business. The price of finished products in winter is several times its cost price, including all the costs of refrigeration units for freezing and storing frozen products. The technology of freezing technology has made it possible to export perishable berries to any country perishable berries to any country in the world, as if the necessary refrigeration containers, the products do not spoil for a long time. When food products or materials are exposed to low temperature, heat is removed products or materials, heat is removed from the surface of the object low-temperature processing is transferred by means of an intermediate coolant to the environment. As a result, the following is achieved the desired effect - cooling, freezing of the object of low-temperature processing or maintaining its temperature aat a certain level. Freezing a product involves cooling it to a temperature significantly lower than the corresponding temperature freezing. Frozen food and raw materials can be stored for many months for many months, i.e. much longer than when using moderately lowered temperatures. This is not only due to the purely quantitative difference in the low-temperature level of the processes of freezing and cold storage processes, but also due to the fact that in frozen most of the moisture is converted into a solid state. Therefore, microorganisms that feed osmotically, i.e. by absorbing liquid by absorption of liquid nutrient media, are deprived of the opportunity to use the ability to use solidified food products containing a very small proportion. The development of modern agriculture, along with obtaining high yields, requires solving the problem of long-term storage and high-quality processing of agricultural products. In this regard, one of the most important of the most important tasks is the development of new technologies for storage and processing of products, which would minimize crop losses, while appearance and useful properties of the products would be preserved in a natural and unchanged throughout the entire shelf life.
Research on cold storage of berries
Keywords: ягода; зберігання; технологія; холод; berry; storage; technology; cold